Finding theology in contemporary Chinese fiction - Jasper, David (International journal for the study of the Christian church, 2019)
Literature can offer a space and hope for a possible creative theology, and this is true also of the contemporary literature of China. In 1923 Lu Xun expressed his hope that literature was capable of transforming the spirit of the Chinese people, Chinese fiction has drawn upon the ancient wisdom of China to explore possibilities after the Cultural Revolution in works that are sometimes banned in the Peoples Republic of China but increasingly have a world readership in English translations. They may be compared with some of the ideas of liberation theology in the western tradition.